Recent Advances in Optimal Adjunctive Antithrombotic Therapy in STEMI Patients Undergoing Primary Angioplasty: An Overview - De Luca, Giuseppe; Suryapranata, Harry (Current Vascular Pharmacology, 2015)
There has been a considerable effort to improve adjunctive antithrombotic therapies to reperfusion strategies in the treatment of ST-segment elevation Myocardial Infarction (STEMI). Therefore, the aim of this article is to provide a critical and updated overview of recent advances on adjunctive antithrombotic therapies in patients undergoing primary angioplasty for STEMI. Due to very low costs, early Unfractionated Heparin (UFH) plus additional periprocedural administration should still be regarded as the gold standard in antithrombotic therapy, whereas subsequent subcutaneous administration of Low Molecular Weight Heparins (LMWHs) or fondaparinux should be considered, especially in patients at higher risk of thromboembolic complications. Periprocedural bivalirudin should be considered instead of a strategy of combined UFH and Glycoprotein (Gp) IIb/IIIa inhibitors, especially among patients at higher risk of bleeding complications. New oral ADP antagonists should be administrated as early as possible soon after diagnosis, whereas the use of clopidogrel should be limited to the cases when the new ADP antagonists are not available or contraindicated. However, rivaroxaban has obtained indication for Acute Coronary Syndromes (ACS), and therefore its combination with aspirin and clopidogrel will gain recognition especially among STSegment Elevation Myocardial Infarction (STEMI) patients. Future trials are needed to compare different possible strategies with oral antithrombotic therapies and in particular optimal duration, especially in the era of new DES that have been shown to reduce the risk of stent thrombosis. Early Gp IIb/IIIa inhibitor use may be considered as upstream therapy especially in high-risk patients, whereas the choice of periprocedural administration may be based on thrombus burden or in case of impaired haemodynamic conditions that may compromise oral drug absorption. Overall, a more aggressive antithrombotic approach should be considered within the first hours from symptom onset, when the considerable viability justifies aggressiveness. The use of radial approach and potential protamine administration should be considered in order to minimize the risk of bleeding complications. Due to the very low mortality currently achieved by primary angioplasty and stenting, a further reduction in short or mediumterm mortality would be not easy to demonstrate. Therefore, additional endpoints, such as infarct size and myocardial perfusion, may be considered in future randomized trials especially for the evaluation of new periprocedural antithrombotic therapies among patients undergoing mechanical revascularization for STEMI.
Keywords: primary angioplasty